The Ethics of Rationing of Critical Care Services: Should Technology Assessment Play a Role? - Eric L. Bloomfield (Anesthesiology Research and Practice)
The costs of health care continue to increase rapidly and steeply in the United States. One area of great expense is that of intensive care units (ICUs). The causes of inflation have not been addressed effectively. ICU resources could become stretched such that they may no longer be available. This paper discusses some of the ethics and concerns behind decision making when providing ICU services in the United States. In particular, the use of electronic records with decision making tools, risk-analysis methods, and documentation of patient wishes for extraordinary care may help with better utilization of resources in the future.